Awards and the Awardees in the contect of Quran = النزل والمنزولون فی السیاق القرآنی - Dr Hafiz Muhammad Badshah; Dr Kifayat-ul-llah Hamdany (Hazara Islamicus, 2018)
Quran is a supreme and rich literature ever found and studied by human beings. It is the perfect literature that carries Sharia, laws with short and long explanations making a considerable space for scholars to speak and share their views with respect to their specialties. Awards and awardees are two terms used many times in Quran but all the way not in the one context that leads to their multiple explanations. In this article, we are going to explain the two terms and their respective meanings in the light of scholarly views of classical and modern Ulema. There are the results and suggestions at the end of the article.